Business cycles, international trade and capital flows: Evidence from Latin America - Guglielmo Maria Caporale; Alessandro Girardi (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper adopts a flexible framework to assess both short- and long-run business cycle linkages between six Latin American (LA) countries and the four largest economies in the world (namely the US, the Euro area, Japan and China) over the period 1980:I-2011:IV. The result indicate that within the LA region there are considerable differences between countries, success stories coexisting with extremely vulnerable economies. They also show that the LA region as a whole is largely dependent on external developments, especially in the years after the great recession of 2008 and 2009. The trade channel appears to be the most important source of business cycle co-movement, whilst capital flows are found to have a limited role, especially in the very short run.
Keywords: C32; E32; F31; F41; 330; International Business Cycle; Latin America; VAR models; Trade and Financial Linkages; Konjunkturzusammenhang; Außenwirtschaft; Kapitalmobilität; Lateinamerika; Internationale Wirtschaftsbeziehungen; USA; Eurozone; Japan; China